Calycosin alleviates ferroptosis and attenuates doxorubicin-induced myocardial injury via the Nrf2/SLC7A11/GPX4 signaling pathway - Han, Quancheng; Shi, Jingle; Yu, Yiding; Yuan, Huajing; Guo, Yonghong; Liu, Xiujuan; Xue, Yitao; Li, Yan (Frontiers in Pharmacology, 2024)
Objective: This study aims to elucidate the regulatory effect of Calycosin on ferroptosis and its influence on the treatment mechanisms of heart failure through in vivo and in vitro experiments.Methods: A rat model of heart failure was induced using doxorubicin, and the cardiac function was evaluated through cardiac ultrasound examination and NT-Pro BNP detection. Myocardial injury was assessed using H&E staining and Masson staining.The extent of mitochondrial damage was evaluated through transmission electron microscopy. Concurrently, the level of ferroptosis was analyzed by measuring ferroptosis markers, including MDA, ferrous ions, the GSH/GSSG ratio, and GPX4 activity. Subsequently, the molecular mechanism by which Calycosin exerts its therapeutic effects in heart failure was investigated through immunofluorescence and Western blotting. Finally, H9c2 cardiomyocytes were treated with doxorubicin to simulate myocardial injury, and the mechanism by which Calycosin mediates its effects in the treatment of heart failure was further verified through Nrf2 gene silencing.Results: Calycosin significantly improves cardiac function in rats, reduces serum NT-Pro BNP levels, and alleviates myocardial cell damage. Additionally, it significantly decreases the levels of ferroptosis in myocardial tissue, as confirmed through transmission electron microscopy and the assessment of ferroptosis markers, including MDA, ferrous ions, GSH, and GPX4 activity. At the molecular level, Calycosin exerts its effects by activating the Nrf2/SLC7A11/GPX4 signaling pathway, evidenced by the upregulation of Nrf2, SLC7A11, GPX4, GSS, and GCL protein expression. This process substantially enhances the antioxidant capacity of rat myocardial tissue and effectively suppresses ferroptosis in myocardial cells. The results obtained from both in vivo and in vitro experiments are consistent. Notably, when Nrf2 is silenced, the protective effect of Calycosin on the myocardium is markedly diminished.Calycosin effectively treats doxorubicin-induced cardiac injury, and its therapeutic effect is likely closely associated with the activation of the Nrf2/SLC7A11/GPX4 signaling pathway and the inhibition of ferroptosis in myocardial cells. Consequently, Calycosin, as a promising compound against doxorubicin-induced cardiotoxicity, warrants further investigation.